المتلازمة الكبدية – الرئوية - الخير محمد; حماد اسماعيل; عكوش عمران (Latakia University Journal -Medical Sciences Series, 2019)
- تضمنت الدراسة (18) مريضاً ، راجعوا المشفى ومعروفين بإصابتهم بتشمع كبدي مشخص بالخزعة، لكشف التظاهرات الرئوية ( سريرياً ، مخبرياً ، شعاعياً ) مع الإشارة لعدم توفر دراسة محلية مماثلة. - توزع المرضى على الشكل الآتي : 14 ذكراً( نسبة 77.77%)،4 إناث ( نسبة 22.22% ). - كانت الكحولية والتهاب الكبد البائي ، السببين الأكثر شيوعاً للتشمع الكبدي عند مرضانا. - كانت الزلة التنفسية بوضعية الراحة والزلة التنفسية بوضعية الانتصاب والتي تخف بالاستلقاء العرضيين الرئويين الأكثر شيوعاً. - أجريت غازات الدم الشرياني وتم حساب المدروج السنخي – الشرياني . - أجريت صورة الصدر الشعاعية البسيطة لكشف تبدلات شبكية – عقدية في قاعدتي الرئتين . - أجري للمرضى اختبار وظائف الرئة، لنفي تناذر حاصر. - أجري ايكو غرافي للقلب لنفي آفة قلبية – رئوية مسببة لنقص الأكسجة ، ولقياس الضغط الرئوي. This research, which studies (18) patients admitted to hospital with hepatic cirrhosis by biopsy, tries to find the pulmonary manifestations (clinical, chemical, and radiological). The study is the first of its kind in Syria. The study included /14/ males (77.77%) and /4/ females (22.22%). It was noticed that Hepatitis B and Alcohol were the most common causes. Dyspnea and platypnea were the most common pulmonary symptoms. Arterial Blood Gas analysis was done and Alveolar-arterial oxygen gradient was calculated. Chest-x-ray was performed to find reticulo-nodular changes in the base of lungs. Pulmonary function test included spirometry for evaluation of any restrictive pattern. Echocardiography was done to evaluate any cardio-pulmonary disease process responsible for Hypoxemia and to measure the pulmonary pressure. The study concluded that two patients had the criteria for HPS (11.11%) and two patients had sub-clinical states.